The Effect of Number of Tourist Visits and Tourism Object Retribution on Local Revenue (Case Study: Tourism, Youth and Sports Office of Tasikmalaya Regency) - Heidi Siddiqa (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the influence of the number of tourist visits and tourist object retribution on Local Revenue (PAD) in the Department of Tourism, Youth, and Sports of Tasikmalaya Regency. This research is conducted because the development of the tourism sector is one way to increase PAD and encourage regional economic development. The research method that can be used to test the influence of the number of tourist visits and torusit object retribution on PAD in Tasikmalaya Regency is quantitative method. The population in this research was 15 data on tourist objects consisting of 3 managers, namely those managed by the Department of Tourism, Youth, and Sports, those in cooperation with the Department of Tourism, Youth, and Sports, and those managed by other parties. The sampling method used is purposive sampling, only those who meet the criteria are used as samples. The results showed that the number of tourist visits and tourist object retribution had a positive and significant effect on Local Revenue (PAD). This shows that tourist visits and tourist object retribution are important factors that can increase PAD in tourist destinations.